Desain Hibrid Menggunakan PID-ANFIS Controller Pada Motor DC Berbasis PSO (Particle Swarm Optimization) - Machrus Ali; Ahmad Ali Syaifudin; Hidayatul Nurohmah (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2021)
DC motors can be used as generators or motors. For this reason, it is necessary to design the best DC motor speed regulation in order to obtain the best optimization. DC motor setting modeling must be adjusted to the DC motor characteristics and setting model. The results of the performance of the DC control model have a different steady-state error, settling time, and overshoot. From the results of running the program, it is found that the PID-PSO-ANFIS hybrid control model produces the best output performance. The results of PID-PSO-ANFIS optimization show that there is no overshot and undershot, settling time is 0.04 seconds, the motor speed reaches a constant and stable state. This design will be developed using artificial intelligence methods and other controllers in order to obtain the best optimization.